Transdisciplinary Indiscernibility and the Sense of Literature (Portuguese version) - Torelly, Gabriel; Zordan, Paola (Nawi, 2023)
The article discusses the problem of the sense inscription in language. Through a bibliographic review, it aims to highlight aporias between the tendencies ofstructuralism and post-structuralism. It is argued that such epistemic systematizations produce incidences in the very notions of method and scientific object. As a specificity, we propose a particular reading of The Logic of Sense and other writings by Gilles Deleuze and his intercessors. Resonances and shifts between the epistemological and expressive thresholds of literature and philosophy are presented. It concluded that such theoretical debates, especially the one presented in The Logic of Sense, induce the sense of philosophy and literature to break with their disciplinary limits and postulate a paradoxical objectity, which we call transdisciplinary indiscernibility.
Keywords: Philosophy; Gilles Deleuze; literature; sense; transdisciplinarity